KORELASI PEMBERDAYAAN DENGAN KEPEMIMPINAN DALAM ORGANISASI PUBLIK - Yustiono1, Eris (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
Empowerment is regarded as a progressive way to enhancing personnel?s competence within an organization. Better personnel?s competence positively corresponds to the ability of the organization in achieving its goal. However, the empowerment may not materialize within an organization without good leadership.A good leader should have the capability to: empower himself, recognize his staff?s potency, and motivate his staff to work, and have confidence in (trust) his staff. Above and beyond good leadership, desire to change on the part of those empowered is also a key factor for the success of empowerment.